Electrochemical study on the corrosion protection behavior of conducting polymer nanocomposites / Magaji Ladan - Magaji , Ladan (2017)
Corrosion is a persistent issue faced by human-made structures made from metals and metal alloys. Steel is used in many structural applications; however, it undergoes severe corrosion when exposed to corrosive media. Coatings are among the best methods to prevent metals and its alloys from the corrosion. However, traditional coating systems such as barrier coatings, metal-rich coatings, and coatings incorporating inhibitors have their setbacks. Conductive polymers such as polypyrrole and polyaniline were used for the corrosion protection of metals. Redox activity and the corrosion-inhibiting ion release ability of conducting polymers make them a good choice in place of hexavalent chromium compounds. However, conducting polymers are porous, stiff, inherent insoluble and low mechanical properties which make them inferior corrosion resistance materials. To tackle the problems associated with the conducting polymers and to harness maximum functionality out of them, conducting polymer nanocomposites (CPNs) were developed. CPNs combine conducting polymers and inorganic pigments in unique methods which exhibit excellent corrosion resistance properties. In this research, nanocomposites of polypyrrole and polyaniline were synthesized by an eco-friendly chemical oxidative polymerization. Core and shell of polyaniline and polypyrrole with titanium dioxide and graphene oxide were prepared and applied for safeguarding steel substrate from corrosion. These nanocomposites were analyzed by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), Field emission scanning electron microscopy (FESEM), energy dispersion X-ray (EDX), Raman spectroscopy, Transmission electron microscopy (TEM) and thermogravimetric analysis (TGA). The TEM results confirmed that the Co-doped TiO2/PPy NTCs, Co-doped TiO2/GO/PANI, and PANI/GO/Zn-doped TiO2 nanocomposites were smaller than TiO2/PPy NTCs, Co-doped TiO2/PANI, and PANI/Zn-doped TiO2, thereby increasing the interaction between the PPy and PANI and the steel surfaces. The corrosion protection ability of the coatings was studied by electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization measurements in 3.5% NaCl solution. The EIS results show that the log |Z| of steel coated with Co-doped TiO2/PPy NTCs, Co-doped TiO2/GO/PANI and PANI/GO/Zn-doped TiO2 NCs reached about 8.2, 9.2 and 9.01, respectively, after 30 days of immersion in 3.5 % NaCl solution. Whereas the log |Z| values of TiO2/PPy, Co-doped TiO2/PANI, and PANI/Zn-doped TiO2 NCs was around 6.0, 7.4 and 7.15, respectively, for the same immersion period. This is likely due to the increased surface areas of the PPy and PANI synthesized in the presence of Co-doped TiO2 NPs, Zn-doped TiO2 and GO respectively. The EIS results are confirmed by the potentiodynamic polarization and open circuit potential values of the Co-doped TiO2/PPy, Co-doped TiO2/PANI, and PANI/Zn-doped TiO2 NCs, which indicated little changes between 1 to 30 days of immersion confirming the protection ability of these coatings. It is evident that the presence of Co-doped TiO2 NPs, Zn-doped TiO2 NPs and GO can enhance the resistance against corrosion at the steel/electrolyte interface.